Detection of the Vulnerable Atherosclerotic Plaque. Pre-Clinical Evaluation of Novel PET Imaging Probes With Experimental Models - Silvola, Johanna (Annales Universitatis Turkuensis D 1030, 2012)
Atherosclerosis is a life-long vascular inflammatory disease and the leading cause of death in Finland and in other western societies. The development of atherosclerotic plaques is progressive and they form when lipids begin to accumulate in the vessel wall. This accumulation triggers the migration of inflammatory cells that is a hallmark of vascular inflammation. Often, this plaque will become unstable and form vulnerable plaque which may rupture causing thrombosis and in the worst case, causing myocardial infarction or stroke. Identification of these vulnerable plaques before they rupture could save lives. At present, in the clinic, there exists no appropriated, non-invasive method for their identification. The aim of this thesis was to evaluate novel positron emission tomography (PET) probes for the detection of vulnerable atherosclerotic plaques and to characterize, two mouse models of atherosclerosis. These studies were performed by using ex vivo and in vivo imaging modalities. The vulnerability of atherosclerotic plaques was evaluated as expression of active inflammatory cells, namely macrophages. Age and the duration of high-fat diet had a drastic impact on the development of atherosclerotic plaques in mice. In imaging of atherosclerosis, 6-month-old mice, kept on high-fat diet for 4 months, showed matured, metabolically active, atherosclerotic plaques. [18F]FDG and 68Ga were accumulated in the areas representative of vulnerable plaques. However, the slow clearance of 68Ga limits its use for the plaque imaging. The novel synthesized [68Ga]DOTA-RGD and [18F]EF5 tracers demonstrated efficient uptake in plaques as compared to the healthy vessel wall, but the pharmacokinetic properties of these tracers were not optimal in used models. In conclusion, these studies resulted in the identification of new strategies for the assessment of plaque stability and mouse models of atherosclerosis which could be used for plaque imaging. In the used probe panel, [18F]FDG was the best tracer for plaque imaging. However, further studies are warranted to clarify the applicability of [18F]EF5 and [68Ga]DOTA-RGD for imaging of atherosclerosis with other experimental models.